PERANAN EKOLABEL DALAM NIAT PEMBELIAN: SUATU STUDI EMPIRIS PADA MEREK THE BODY SHOP - Vincent Riyanto; Sharon B. Soesanto; Sabrina O. Sihombing (MIX: JURNAL ILMIAH MANAJEMEN, 2018)
This research aims to assess the relationship between behavioral variables on the environment: ecolabel awareness, trust, ecolabel knowledge, ecolabel availability, and environmental concerns of intention to buy. Data was collected through questionnaires with non-probability sampling method which included a total sample of 230 respondents. Hypothesis testing was conducted by applying Structural Equation Modeling (SEM). The results shows that there are six out of ten supported hypotheses and four unsupported hypotheses. The six hypotheses supported are (1) there is positive relationship between attitude and trust in buying environmentally friendly product, (2) there is positive relationship between ecolabel awareness and ecolabel attention, (3) there is positive relationship between ecolabel awareness and intention to buy, (4) there is positive relationship between  trust in buying environmentally product and ecolabel attention, (5) there is positive relationship between trust in buying environmentally product and intention to buy, and (6) there is positive relationship between ecolabel availability and  ecolabel attention. This research also contributes theoretical contributions, managerial implications, and recommendations for further research